hubungan antara berat badan dengan tekanan darah pada orang dewasa usia 20-50 tahun di RT.08/RW.04 Dusun Pulorejo, Desa Bening, Kecamatan Gondang, Kabupaten Mojokerto - Zainuri, Imam; Laili Dian Novita (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Blood pressure is the power produced by the blood in each mm2unit of the blood vessel (Guyton and Hall, 1997). According to Kamus Besar Bahasa Indonesia, body weight is great pressure of the thing (body) when it’s lifted or measured. The blood pressure of fat people is higher than the blood pressure of thiny people (Dr.G.Beevers,2002). The purpose of this research to know the correlation between body weight and blood pressure toward adult people at Rt 08 Rw 04 Pulorejo Village Bening Village Gondang Subdistrict Mojokerto District. This research is an analitic research. The population is the adult people at RT 08 RW 04 Pulorejo Village Bening Village Gondang Subdistrict Mojokerto District (45 people). The sample is taken at the number of 45 people using total sampling method. The instruments used in collecting the data of this research are scales Soehnle brand, sphygmomanometer mercury Tens brand and stethoscope Onemed brand. The data of this research is gained through questionnaire, including the age, the gender and the illnes of the respondents. The specific data includes the body weight measurement and the blood pressure measurement. Based on the research conducted to 45 respondents there are not correlation between body weight and blood pressure toward adult people at RT 08 RW 04 Pulorejo Village Bening Village Gondang Subdistrict Mojokerto District, woman respondent more have high blood pressure than man respondent. It’s caused by an effect of a hormonally, expecially esterogen and progesteron hormon just have by a woman.Key words : body weight, blood pressure, adult people